Long-term effects of embryonic exposure to contaminants in zebrafish - Correia, Daniela Veloso da Conceição Soares (2018)
Nowadays, the aquatic environment is contaminated by various environmental pollutants, in quantities of a very reduced range. This type of scenario, called a realistic environmental exposure scenario, has an important relevance because the adverse effects it produces are not immediately perceptible, may only manifest in later development stages and also in very sensitive parameters such as behavioral level. In this work we intend to evaluate the effects of sublethal concentrations of carbaryl, a carbamate insecticide, on the behavior of adult zebrafish, which were exposed in the embryonic stage to carbamate. After acute exposure to various concentrations of carbaryl, the organisms completed their development into adulthood in a clean environment. Therefore, several behavioral tests were carried out, namely locomotor activity and thigmotactic behavior, exploratory swimming, feeding behavior, social behavior (shoal) and avoidance behavior to predators. In the test aimed at locomotor activity and thigmotactic behavior, the locomotor response of the pre-exposed organisms was affected, swimming a smaller distance, mainly in the presence of a light stimulus and the fish exposed to the higher concentration showed a decrease of the thigmotactic behavior in the dark periods, with no habituation to the stimuli over time. In the exploratory swimming test, fish exposed to the highest concentration had a lower tendency to explore the surface, remaining closer to the bottom. The feeding test, the higher concentrations had a longer time in the total food intake. In the social behavior test, it was observed in the fish exposed to the higher concentration a greater tendency to remain closer to the shoal. However in the predator avoidance test and in the reproduction and development of F1, our data do not allow us to conclude if pre-exposure to carbaryl affected zebrafish. All of these results may be evidence of a disruption in various physiological and biochemical processes. In general, the data obtained in this study show that exposure to carbaryl during embryonic development may induce long-term effects such as behavioral changes. This scenario has an important ecological relevance that should be taken into account in future risk assessments.